Smoothed-Particle Hydrodynamics (SPH) Simulation of AA6061-AA5086 Dissimilar Friction Stir Welding - Hamed Jamshidi Aval (Metals, 2023)
The present study investigates thermo-mechanical issues associated with the dissimilar friction stir welding process of AA6061 and AA5086 aluminum alloys through smoothed-particle hydrodynamics (SPH) simulation and experimental investigations. The results demonstrate that the presented model accurately predicts the thermal history during the friction stir welding process. Furthermore, both simulation and experimental data indicate that when the AA6061 alloy is located on the advancing side, the temperature profile is drawn towards the AA6061 alloy. Conversely, the temperature profile is more symmetrical when the AA6061 alloy is positioned on the retreating side. Additionally, simulation results reveal that when the AA5086 alloy is on the advancing side, the strain rate distribution between the advancing and retreating sides is nearly symmetrical. When the AA5086 alloy is placed on the advancing side, the temperature and strain rate on the advancing side are higher than on the retreating side, compared to when the AA5086 alloy is located on the retreating side.